Identifying (with) 'Carlota': myths, metaphors and landscapes of Cuban Africanía, 1974-1980 - Peters, Christabelle A. (2010)
The thesis expands the field of scholarly enquiry on the Cuban intervention in Angola beyond the frame of geopolitics into the area of cultural politics. It considers the relation between Africa as a cultural and political `territory' in the Cuban imaginary and the epic internationalist mission known as Operation Carlota. By focusing on representations and manifestations of 'Africanness' in discursive practices ranging from culture and the arts to domestic and foreign policy, the enquiry illustrates how the notion of Cuba as Latin-African evolved in relation to changes in revolutionary ideology during the period known as the quinquenio gris, and with regard to the swell of liberation movements throughout the African Diaspora.